Effects of high- versus low-intensity lipid-lowering treatment in patients undergoing serial coronary computed tomography angiography: results of the multi-center LOCATE study - Weichsel, Loris; André, Florian; Renker, Matthias; Breitbart, Philipp; Overhoff, Daniel; Beer, Meinrad; Giesen, Alexander; Vattay, Borbála; Buß, Sebastian Johannes; Marwan, Mohamed; Schlett, Christopher L.; Giannopoulos, Andreas A.; et al. (Clinical research in cardiology, 2024)
To evaluate the effects of lipid-lowering medications of different intensities on total, calcified, and non-calcified plaque volumes in patients undergoing serial cardiac computed tomography angiography (CCTA).
Online veröffentlicht: 30. Juli 2024
Mitglieder von The LOCATE Investigators: Sorin Giusca, Moritz Schütz, Lukas D. Weberling, Ramona Schmitt, Stefan O. Schoenberg, Mustafa Kuru, Steffen Klömpken, Szilveszter Balint, Pal Maurovitch-Horvat, Johannes Görich, Mustafa Emami, Philipp A. Kaufmann, Patrick Doeblin, Natalia Solowjowa, Karl Jakob Weiss, Stefan Baumann, Ksenia Stach
Gesehen am 19.11.2024
Kenija Stach ist fälschlich als Ksenia Stach geschrieben